OSSE dataset for assessing the sensitivity of pCO2 reconstructions to sampling scales across a Southern Ocean sub-domain - Djeutchouang, Laique Merlin; Chang, Nicolette; Gregor, Luke; Vichi, Marcello; Monteiro, Pedro M. S. (Zenodo, 2021)
The data stored in this repository are part of themanuscript entitled "The sensitivity of pCO 2 reconstructions to sampling scales across a Southern Ocean sub-domain: a semi-idealized ocean sampling simulation approach" submitted in consideration for publication for inEuropean Geosciences Union: Biogeosciences. The netcdf file includes oceanographic (physical + biogeochemical) data, namely the partial pressure of carbon dioxide (pCO 2 ) data at the surface ocean from the high-resolution (±10km) forced NEMO-PISCES coupled ocean model (BIOPERIANT12) and from the semi-idealized observing system simulation experiments (OSSEs) we performed.